Illumination Dependent Electrical Data Identification of the CdZnO Interlayered Metal-Semiconductor Structures - Tan, S. O.; Tascioglu, I.; Altindal Yeriskin, S.; Tecimer, H.; Yakuphanoğlu, Fahrettin (Springer, 2020)
Electrical data of the Schottky structure with CdZnO interlayer have been evaluated for different illumination intensities. Considering such parameters as, the ideality factor (n), reverse saturation current (I-o), zero bias barrier height (phi(Bo)), series and shunt resistances (R-s and R-sh) and surface states (N-ss), we concluded that these parameters extremely depend on the illumination power and applied bias voltage. In consequence of the Ohm's law and Norde's method used for R-s determination, the R-s values decreased with increasing illumination intensity. The energy distribution of the N-ss and voltage dependent profile of resistance (R-i) of the structure were extracted from the forward bias current-voltage (I-V) data. The fabricated CdZnO interlayered metal-semiconductor structure appears to have photodiode behavior. Accordingly, the alteration in the basic electrical parameters by the increment in illumination levels indicates that, the carrier generation takes place in the depletion layer and the conductivity of the CdZnO interlayered structure is improved.
Keywords: Nanostructures; Electrical data; Schottky photodiodes; CdZnO interlayer; Illumination; Surface states